Photodegradation Pathways of Typical Phthalic Acid Esters Under UV, UV/TiO2, and UV-Vis/Bi2WO6 Systems - Wang, Chunying; Zeng, Ting; Gu, Chuantao; Zhu, Sipin; Zhang, Qingqing; Luo, Xianping (Frontiers in Chemistry, 2019)
Photolysis and photocatalysis of typical phthalic acid esters (dimethyl phthalate, DMP; diethyl phthalate, DEP; dibutyl phthalate, DBP) were carried out in UV, UV/TiO2, and UV-Vis/Bi2WO6 systems. All of the selected phthalic acid esters and their decomposition byproducts were subjected to qualitative and quantitative analysis through HPLC and GC-MS. The results of 300 min of photolysis and photodegradation reaction were that each system demonstrated different abilities to remove DMP, DEP, and DBP. The UV/TiO2 system showed the strongest degradation ability on selected PAEs, with removal efficiencies of up to 93.03, 92.64, and 92.50% for DMP, DEP, and DBP in 90 min, respectively. UV-Vis/Bi2WO6 had almost no ability to remove DMP and DEP. However, all of the systems had strong ability to degrade DBP. On the other hand, the different systems resulted in various byproducts and PAE degradation pathways. The UV system mainly attacked the carbon branch and produced o-hydroxybenzoates. No ring-opening byproducts were detected in the UV system. In the photocatalytic process, the hydroxyl radicals produced not only attacked the carbon branch but also the benzene ring. Therefore, hydroxylated compounds and ring-opening byproducts were detected by GC-MS in both the UV/TiO2 and UV-Vis/Bi2WO6 photocatalytic systems. However, there were fewer products due to direct hole oxidation in the UV-Vis/Bi2WO6 system compared with the UV/TiO2 system, which mainly reacted with the pollutants via hydroxyl radicals.